Single Stage Transanal Pull-Through for Hirschsprung's Disease in Neonates: Our Early Experience - Pradeep Bhatia; Rakesh S Joshi; Jaishri Ramji; Mitesh Bachani; Amit Uttarwar (EL-Med-Pub, 2013)
Objective: Hirschsprung's disease is one of the common causes of intestinal obstruction in neonates. Transanal endorectal pull-through represents the latest development in the concept of the minimally invasive surgery for Hirschsprung's disease. In this study, we present our early experience with single stage transanal pull through in neonates. Design: Retrospective study of neonates with single stage transanal pull-through done for Hirschsprung's disease in our institute from January 2011 to January 2013. Material and Method: Five newborn boys who presented with Hirschsprung's disease were studied. The selection criteria included radiological transition zone at rectosigmoid or mid-sigmoid region, weight more than 2 kg, no evidence of enterocolitis or sepsis and no associated major anomaly. Single stage transanal endorectal pull-through was done in these patients. The follow-up period ranged from 6 months to 2 years. Results: Five patients with a mean age of 26.4 days (range 15-45 days) and a mean weight of 2.6 Kg (range 2.2 to 3.7 Kg) underwent transanal endorectal pull through. The mean operating time was 68 min (range 60 to 120 min). The average intra-operative blood loss was 20 ml (range - 10 to 30 ml) and the average length of bowel resected was 12.8 cm (range - 10 to 18 cm). Post-operatively patients passed first stool between 2nd and 3rd day. Oral feeding was resumed on 5th to 6th post-operative day. The average post-operative duration of stay in hospital was 10 days. None of the patients had post-operative bleeding, urethral injury, anastomotic leak or retraction of anastomotic site. Three patients developed perianal excoriation and one patient had post-operative enterocolitis. No mortality occurred in the series. Conclusion: Advancement in pediatric anaesthesia, availability of pediatric surgical expertise, improvement in pre-operative and post-operative management and nursing care has made single stage transanal pull-through in neonates a feasible option. The early results are comparable to single stage or multistage surgery in older children.